Madeline Haller: capstone - Haller, Madeline, artist (Colorado State University. Libraries, 2024)
The artist's statement: Throughout my life, I have found that nothing is ever just one thing. Nothing fits into one single category, and lives there undisturbed forever. Everything changes, grows, adapts and represents more than its first impression. Simplicities and complexities are woven into the very fibers of our lives. These fibers are meant to support not only who we are meant to be in the future, but also the heavier parts of our pasts that have been soaked in the experiences we have to look back on. This is why the structure of our lives as well as the things in it cannot be described using simple words and instead must eloquently acknowledge the individuality of everything that surrounds us. As an artist, I have a great affinity for a minimalistic, simpler design style and much of my work reflects this. Line work, solid colors, simple designs, all very much a part of the art that lives close to my heart. Now, being that I too am a creature who cannot simply be shoved into the box of single categories, I also am always very attached to designs that depict deeper meanings, intensities, bold colors and artistic choices that don't follow the norms of society. I feel, to my core, that the most beautiful things in life come from "the in betweens". Nature is a source of inspiration for countless reasons, but most definitely due to its ever changing, beautiful unbiased existence. The artistic media that can be found in nature is another source of beauty and inspiration itself. I have spent many semesters studying as a metalsmith through our Colorado State Metals program and have found a deep admiration for the physical arts and humanities. I feel that my adoration of the subject and the practice of molding the elements into art has deepened my attention to detail. It is in fact possible to find precision amongst chaos and complex ideas. I now am much more inclined to focus on subtle detailing in the art I produce for my degree path. That degree path being Graphic Design. Graphic design, in my opinion, is both a technical art form as well as one of the most freely expressive. Quite literally anything you imagine can be created through practice and the ability to manipulate the programming and applications intended for designers and creatives. I'd like to think I have a broad imagination and I believe, though my art is in fact structured, no two pieces are the same. I feel as though each piece I create is for a specific purpose and yet I could change and rearrange them until the end of time coming up with new ideas and sharpening my craft. As my career progresses, I intend to collect new interests and inspirations. I know that as a person I have changed and matured as a woman and as an artist. In a world full of unique and creative people, I strive to be nothing short of myself.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design